Meningkatkan Kompetensi Guru Dalam Membimbing Siswa SMP Menyelesaikan Soal OSN Matematika - Azhar, Ervin; Darmawati, Desak Made; Umam, Khoerul (TAAWUN, 2023)
The role of the teacher is not only teaching but also training other academic skills such as solving OSN questions. It would be a shame if the teacher could not guide students in solving OSN questions. According to DKI Jakarta Elementary and Elementary Education data, there has not yet been a Muhammadiyah school that has won OSN, both at the Kotip level, let alone at the provincial and national levels. This Community Service activity aims to increase the competence of Muhammadiyah Middle School Mathematics Teachers under the auspices of the Jakarta PWM Elementary Education Council to guide students in solving OSN questions. The training activities include: (1) the prites stage; (2) the difficulty analysis stage; (3) the stage of giving tricks; and (4) the percentage stage. This activity has been carried out and received good enthusiasm from partners. Partners in this case are Mathematics teachers at Muhammadiyah Middle Schools throughout DKI. It is proven that there was an increase in the teacher’s ability to work on OSN questions that occurred in this training. This can be seen from the more participants who were able to do the Posttest questions correctly after being given training by UHAMKA Mathematics Education lecturers. The seriousness of the participants in this training was evident from the collection of video presentations that were sent by the participants as many as 5 videos a day.